Lrp12/Mig13a Reveals Changing Patterns of Preplate Neuronal Polarity during Corticogenesis that Are Absent in Reeler Mutant Mice - Schneider, Stephanie (Oxford University Press, 2011)
During corticogenesis, the earliest generated neurons form the preplate, which evolves into the marginal zone and subplate. Lrp12/Mig13a, a mammalian gene related to the Caenorhabditis elegans neuroblast migration gene mig-13, is expressed in a subpopulation of preplate neurons that undergo ventrally directed tangential migrations in the preplate layer and pioneer axon projections to the anterior commissure. As the preplate separates, Lrp12/Mig13a-positive neurons polarize in the radial plane and form a pseudocolumnar pattern, prior to moving to a deeper position within the emerging subplate layer. These changes in neuronal polarity do not occur in reeler mutant mice, revealing the earliest known defect in reeler cortical patterning and suggesting that the alignment of preplate neurons into a pseudolayer facilitates the movement of later-born radially migrating neurons into the emerging cortical plate.